(untitled) (Research, Society and Development, 2020)
When considering school Geography importance and concept of place centrality in the Geography teaching, for the early years of Elementary Education, we present a proposal for the development of a pedagogical workshop as a possibility to work with this concept in the stage of Basic Education. In this sense, from a theoretical survey, we approach the importance of teaching Geography in the early years and the development of pedagogical workshops as a possibility of teaching to encourage pedagogical practices that allow the student to build geographic knowledge and all together, perceive and analyze your reality critically. Furthermore, we highlight that the proposed pedagogical workshop can be a relevant learning tool that seeks to promote the articulation between theoretical knowledge and the practical development of what has been studied. When developing it, taking into account the student’s reality, the teacher provides on a teaching process whose learning can be more effective and meaningful for the student.